Meningkatkan Pemahaman Siswa Menggunakan Model Pembelajaran Kooperatif Tipe Numbered Heads Together (NHT)Pada Mata Pelajaran IPS Kelas IV SD Negeri 011 Rambah Hilir Tahun Ajaran 2015/2016 - Jawahir Jawahir (STKIP Rokania Pasir Pangaraian, 2018)
Abstract, Social Sciences (IPS) as an integral part of the curriculum of learning in schooling, should be delivered in an interesting and meaningful way by integrating all components of learning effectively. In practice the learning should always pay attention to the developing context. This type of research is a classroom action research consisting of planning, implementation, observation and reflection. This study consists of two cycles consisting of two meetings in each cycle. Data analysis techniques by observing student learning activities and student learning outcomes. The result of the research shows that the increase of students understanding from the learning result tends to increase to be better. The average change in student learning outcomes from 45.6 to 85.0. The percentage of completeness reaches the target that the researcher wants to happen in the second cycle at the second meeting by 89%. Then it can be concluded that the Model of cooperative learning type Numbered Heads Together (NHT) can improve the understanding of students learning grade IV SD Negeri 011 Rambah Hilir